Elaboramos propuestas de refrigerios saludables - Quispe Robles, Eliana Mercedes (2019)
The present sufficiency work has been prepared for children of the fifth grade of Primary Education of the Educational Institution No. 81017 Santa Edelmira of the city of Trujillo in the year 2019, with the theme entitled: We prepare a sprout to improve the nutrients of our diet in which the competition is going to develop: design and build technological solutions to solve problems of your environment. In the preparation of the session, work has been carried out taking into account the didactic processes of the area of Science and Technology such as: Problem statement, solution planning, prototype design, construction and validation of the prototype, structuring of knowledge built in response to the problem , evaluation and communication. The strategies used were designed to promote the active and meaningful participation of all students, as well as rescue the use of new learning in their daily lives. It is intended at all times to maintain the interest and motivation of the student for the topic to be developed since it is a very important area that seeks students to develop life skills.